ROZWÓJ ZAWODOWY NAUCZYCIELI JĘZYKA KASZUBSKIE-GO – DIAGNOZA POTRZEB DOTYCZĄCYCH SZKOLEŃ - Radzimińska, Lucyna; Stanulewicz, Danuta (Neofilolog, 2019)
The Kashubian language was introduced as a school subject in 1991. In the school year 2013/2014, the number of students attending Kashubi-an classes amounted to 17,145. They were taught the language by ca. 620 teachers in 420 schools: 13,850 in 293 primary schools, 2,688 in 103 junior secondary schools and 607 in 24 senior secondary schools. The aim of this paper is to present the results of a questionnaire investi-gating the training needs of Kashubian teachers. It appears that they would willingly attend courses or workshops in all the areas mentioned in the questionnaire, including, inter alia, language teaching methodolo-gy as well as Kashubian literature, culture and history. It is no surprise that the demand for such courses is so high since the core curricula for all school levels emphasize the importance of teaching Kashubian cul-ture, history and geography alongside the Kashubian language.